Bionic gradient zirconia reinforced resin block, post and core and its design method and application

By optimizing the material combination of resin matrix and zirconia and optimizing the design using finite element model, zirconia reinforced resin blocks with bionic gradient structure were prepared, which solved the problem of uneven stress distribution of existing resin pile core materials and improved repair Effects and clinical lifespan.

CN118557445BActive Publication Date: 2025-02-18HOSPITAL OF STOMATOLOGY SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410668150.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-02-18
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

The existing resin pile core materials lack a bionic gradient structure, resulting in uneven stress distribution, affecting the repair effect and clinical service life.

Method used

By optimizing the surface modification of the resin matrix and zirconia, a zirconia-enhanced composite resin material with different elastic modulus is constructed, and the finite element digital model is used to optimize the layering and elastic modulus design of the gradient pile core, and layered stacking is used to optimize the layering and elastic modulus design of the gradient pile core. Technology prepares bionic gradient zirconia reinforced resin blocks.

Benefits of technology

The bionic gradient structure of resin pile core materials is realized, the uniformity of stress distribution and the bionicity and stability of repair effects are improved, and the clinical service life of pile cores is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118557445B_ABST
    Figure CN118557445B_ABST
Patent Text Reader

Abstract

The present invention discloses a bionic gradient zirconia reinforced resin block, a post and core, and a design method and application thereof. The design method first obtains a zirconia reinforced composite resin material with fluidity, processability, and different elastic moduli by optimizing the resin matrix and modifying the surface of zirconia, further optimizes and adjusts the layering and elastic modulus design of the gradient post and core using a finite element digital model, and then uses a layered stacking technology to prepare a bionic gradient zirconia reinforced resin block according to the preferred design; the design method enables the resin block to better meet the requirements of the elastic modulus gradient distribution of natural dentin itself, and improves the bionics and stability of the repair effect. The bionic gradient zirconia reinforced resin post and core prepared by the present invention not only has personalization, integration, bionics, aesthetics, biocompatibility, and good mechanical properties, but can also be widely used in the field of tooth defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dental restorative materials, and in particular relates to a bionic gradient zirconia reinforced resin block, a post and core, and a design method and application thereof. Background Art

[0002] Large-area tooth defects caused by caries, trauma, and other reasons are common in oral clinical work. They often need to be repaired with post-core crowns after completing root canal treatment to provide retention for the affected teeth and improve the tooth's fracture resistance. Prefabricated fiber-reinforced resin posts have been widely used in clinical practice because of their good aesthetics and elastic modulus close to natural dentin. Although the finite element stress distribution of fiber post-repaired teeth is more uniform compared with metal posts and cores with high elastic modulus, and in vitro tests also show good mechanical properties. However, in clinical studies, teeth repaired with fiber posts after root canal treatment still have a failure rate of 2% to 40%. This large range of failure rates is attributed to many variables, including the variability of the restored tooth position, the variability of the root canal anatomical morphology, and the variability of the final restoration method. Therefore, it is of great clinical significance to prepare personalized post and core materials that match natural teeth.

[0003] With the increasing application of CAD / CAM technology in the oral field, integrated posts and cores are a new development direction for post and core restoration systems because they combine the personalized appearance of cast posts and cores with the superior biological and aesthetic properties of fiber-reinforced resins. In recent years, due to the innovation and improvement of composite material manufacturing and curing processes, the proportion of resin composite blocks used for indirect restoration has greatly increased. Currently, the commercialized resin composite blocks mainly include Paradigm MZ100, Lava Ultimate, Trinia and Cerasmart. Resin-based materials have better machinability and edge adaptability due to their lower brittleness, less crack formation and expansion during processing. Resin composite blocks have been used to produce veneers, inlays, crowns, posts and cores and other restoration materials in the dental field.

[0004] It is worth noting that natural teeth are a gradient structure, showing the characteristics of elastic modulus gradient distribution. It is reported that the elastic modulus of dentin at the cervical part of the tooth is about 20.11GPa, about 18.03GPa in the middle of the root, and about 16.45GPa in the apex, showing a trend of decreasing elastic modulus from the crown to the apex. Although the elastic modulus of the CAD / CAM resin blocks currently on the market is close to that of dentin, it is still a uniform elastic modulus and does not have a bionic gradient. Studies have shown that local slight differences between materials with different elastic moduli will also affect the distribution of stress-strain, resulting in stress concentration. This is also one of the main reasons for the high restoration failure rate in clinical studies. Therefore, designing a resin block with a bionic gradient and a bionic gradient resin post and core system to personalize the structure and mechanical properties of the tooth, thereby improving its clinical service life, is an urgent problem to be solved by the current post and core restoration materials. Summary of the invention

[0005] In order to overcome the deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide a design method for a bionic gradient zirconia reinforced resin block. The design method first obtains a zirconia reinforced composite resin material with fluidity, processability and different elastic moduli by optimizing the resin matrix and modifying the surface of zirconia, and further uses a finite element digital model to optimize and adjust the layering and elastic modulus design of the gradient post and core, and then uses a layered stacking technology to prepare a bionic gradient zirconia reinforced resin block according to the preferred design; the design method enables the resin block to better meet the requirements of the elastic modulus gradient distribution of natural dentin itself, thereby improving the bionics and stability of the repair effect.

[0006] The second object of the present invention is to provide a bionic gradient zirconia reinforced resin block obtained by the above-mentioned design method.

[0007] The third object of the present invention is to provide a bionic gradient zirconia reinforced resin post and core, which is obtained by CAD / CAM cutting of a bionic gradient zirconia reinforced resin block, and has individuality, integration, biomimetic, aesthetic, biocompatibility and good mechanical properties. The bionic gradient zirconia reinforced resin post and core described in the present invention can also be referred to as a gradient post and core.

[0008] The fourth objective of the present invention is to provide the application of the above-mentioned bionic gradient zirconia reinforced resin post and core in the field of tooth defect repair.

[0009] The primary purpose of the present invention is achieved through the following technical solutions:

[0010] A design method for a bionic gradient zirconia reinforced resin block comprises the following steps:

[0011] (1) Construction of a zirconia reinforced composite resin material system: 20-40wt% of a resin matrix and 60-80wt% of a reinforcing filler are stirred in a vacuum tube degassing mixer, and stored away from light for later use. A zirconia reinforced composite resin material with processability and different elastic moduli can be obtained through a preliminary light curing treatment, a subsequent curing treatment, and a heating treatment;

[0012] (2) Model design of bionic gradient zirconia reinforced resin post and core: Use Solidworks software to build a post-core-crown restoration model, and further import the model into the finite element analysis software Ansys Workbench for stress analysis; set the gradient post and core layering to a three-stage design, assign the elastic modulus values ​​of different zirconia reinforced resins obtained in step (1) to the gradient post and core, and assign material properties to other parts of the model, and mesh the model. Then, apply static loads to simulate the force on the teeth during chewing, analyze the stress distribution inside the teeth, adjust and optimize the layering and elastic modulus properties of the gradient post and core until the stress is evenly distributed inside the teeth, so as to screen out a bionic gradient post and core model that matches the tooth gradient;

[0013] (3) Preparation of bionic gradient zirconia reinforced resin block: The zirconia reinforced resin with different elastic moduli obtained in step (1) is injected into a stainless steel mold according to the layered design of the bionic gradient post and core obtained in step (2). After each 1 mm of material is injected, a preliminary photocuring treatment is performed, and then the next layer of material is injected and the above curing process is repeated until the entire mold is filled. The resin block is then taken out of the stainless steel mold, and subjected to post-curing treatment and heat treatment to finally obtain a bionic gradient zirconia reinforced resin block.

[0014] Preferably, the resin matrix in step (1) consists of 97-99.5wt% of resin monomers and 0.5-3wt% of photoinitiator; the resin monomers consist of (30-70)wt%: (30-70)wt% of urethane dimethacrylate (UDMA) and triethylene glycol dimethacrylate (TEGDMA); the photoinitiator consists of (40-60)wt%: (40-60)wt% of camphorquinone (CQ) and N,N-dimethylaminoethyl methacrylate (DMAEMA).

[0015] Preferably, the resin matrix is ​​prepared by mixing the resin monomer and the photoinitiator, placing the mixture on a shaker at a speed of 80 to 120 rpm / min, and shaking and mixing for 48 to 72 hours in the dark.

[0016] Preferably, the reinforcing filler in step (1) comprises 0-10 wt % of silanized nano zirconium oxide and 90-100 wt % of dental glass powder.

[0017] Preferably, the preparation process of the silanized nano zirconium oxide is as follows: nano zirconium oxide (50-100 nm), pure water, anhydrous ethanol and silane coupling agent (KH570) are prepared according to a mass volume ratio of 1-5 g: 100 ml: 100 ml: 5 mL; firstly, nano zirconium oxide (50-100 nm), pure water and anhydrous ethanol are ultrasonically mixed for 30-60 min, and the silane coupling agent (KH570) is added dropwise; magnetic stirring is performed at 60-80° C. for 6-12 h, and the mixture is allowed to stand overnight; the supernatant is removed, the mixture is centrifuged at 5000-10000 rpm for 10-30 min each time, and the mixture is washed with anhydrous ethanol for 5 times, and the powder is collected; the mixture is dried at 50-80° C., ground into powder, and the silanized nano zirconium oxide is prepared;

[0018] The dental glass powder is composed of 10 wt% aluminum oxide, 10 wt% boron oxide, 25 wt% barium oxide and 55 wt% silicon dioxide; the dental glass powder used in the present invention is produced by SCHOTT.

[0019] Preferably, the stirring time in step (1) is 30 min and the light-proof temperature is 4°C.

[0020] Preferably, the preliminary curing treatment in step (1) is performed using a radiation intensity of 1400 to 1500 mW / cm 2 Use an LED curing lamp to irradiate the material surface at 0-1mm for 40s; the subsequent curing treatment temperature is 37-60℃ and the time is 12-24h; the heating treatment temperature is 120-180℃ and the time is 12-24h.

[0021] Preferably, the three-dimensional finite element model of post-core-crown restoration described in step (2) can be a model of different tooth defect types (two-wall, three-wall, four-wall) or different tooth position defects (anterior teeth, premolars, molars).

[0022] Preferably, the three-stage design in step (2) is specifically as follows: the thickness of the first layer is 5 to 7 mm, the thickness of the second layer is 3 to 5 mm, and the thickness of the third layer is 3 mm; the three-stage design of the elastic modulus is: 9.8 to 20 GPa for the first layer, 8.5 to 18 GPa for the second layer, and 6.7 to 16 GPa for the third layer; the static load is 50 to 400 N, and the loading direction is horizontal loading, vertical loading or oblique loading.

[0023] Preferably, the stainless steel mold in step (3) is a stainless steel mold with a length of 13.0-14.0 mm, a width of 11.0-12.0 mm, and a height of 17.0-18.0 mm and a scale marking 0-1.0 mm inside.

[0024] Preferably, the preliminary light curing treatment in step (3) is performed using a radiation intensity of 1400 to 1500 mW / cm 2Use an LED curing lamp to irradiate 9 points at 0-1mm on the surface of the material, and irradiate each point for 80s; the post-curing treatment temperature is 37-60℃ and the time is 12-24h; the heat treatment temperature is 120-180℃ and the time is 12-24h to make it completely cured.

[0025] The second object of the present invention is achieved by the following technical solutions:

[0026] A bionic gradient zirconia reinforced resin block is designed by the above design method.

[0027] The third object of the present invention is achieved by the following technical solutions:

[0028] A bionic gradient zirconia reinforced resin post and core is obtained by cutting a bionic gradient zirconia reinforced resin block through CAD / CAM.

[0029] The resin post and core prepared by the present invention not only has personalized and integrated performance, but also has elastic modulus gradient bionic characteristics matching the root dentin.

[0030] The fourth object of the present invention is achieved by the following technical solutions:

[0031] Application of a bionic gradient zirconia reinforced resin post and core in the field of tooth defect restoration.

[0032] Preferably, the application is specifically: application of the bionic gradient zirconia reinforced resin post and core in different tooth defect types (two-wall, three-wall, four-wall) or different tooth defect models (anterior teeth, premolars, molars).

[0033] Compared with the prior art, it has the following advantages and beneficial effects:

[0034] (1) The present invention obtains a zirconia reinforced composite resin material with fluidity, processability and different elastic moduli by optimizing the resin matrix and modifying the surface of zirconia. The finite element digital model is further used to optimize the layering and elastic modulus design of the gradient post and core. Subsequently, the layered stacking technology is used to prepare a bionic gradient zirconia reinforced resin block according to the preferred design. Based on this, a bionic gradient zirconia reinforced resin post and core system is constructed, thereby better meeting the requirements of the artificial post and core restoration system for the elastic modulus gradient distribution of natural dentin itself, and improving the bionics and stability of the restoration effect.

[0035] (2) The present invention adopts CAD / CAM to cut bionic gradient zirconia reinforced resin blocks to prepare zirconia reinforced resin posts and cores with bionic gradients. The personalized post and core morphology is designed by CAD to match the root canal morphology, and the layered design and elastic modulus design of the gradient post and core screened out by the finite element digital model are combined. Finally, the gradient resin block is cut by CAM to obtain a personalized gradient post and core that matches the tooth.

[0036] (3) The bionic gradient zirconia reinforced resin post and core prepared by the present invention not only has the advantages of personalization and integration, but also has the bionic characteristics of elastic modulus gradient matching the root dentin, effectively improving the clinical prognosis of the post and core restoration system.

[0037] (4) The present invention verifies the flexural strength and restorability of bionic gradient zirconia reinforced resin posts and cores through an in vitro tooth fracture resistance experiment of bionic gradient zirconia reinforced resin posts and cores, providing a basis for their clinical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The stress distribution cloud diagram in the finite element model of the gradient post-core (6-4-3 mm layering, 9.8-8.5-6.7 GPa elastic modulus) designed for Example 1; wherein, Figure 1 (A) is the distribution of equivalent stress from the crown to the root along the pile-surrounding structure interface; Figure 1 (B) is the distribution of equivalent stress from buccal to lingual side along the red line in the cross section;

[0039] Figure 2 This is an interface diagram of the bionic gradient zirconia reinforced resin block prepared in Example 1;

[0040] Figure 3 The stress distribution cloud diagram in the finite element model of the gradient post-core (5-5-3 mm layering, 9.8-8.5-6.7 GPa elastic modulus) designed for Example 2; wherein, Figure 3 (A) is the distribution of equivalent stress from the crown to the root along the pile-surrounding structure interface; Figure 3 (B) is the distribution of equivalent stress from buccal to lingual side along the red line in the cross section;

[0041] Figure 4 The stress distribution cloud diagram in the finite element model of the gradient post-core (7-3-3 mm layering, 9.8-8.5-6.7 GPa elastic modulus) designed for Example 3; wherein, Figure 4 (A) is the distribution of equivalent stress from the crown to the root along the pile-surrounding structure interface; Figure 4 (B) is the distribution of equivalent stress from buccal to lingual side along the red line in the cross section;

[0042] Figure 5The stress distribution cloud diagram in the finite element model of the gradient post-core (6-4-3 mm layering, 20-18-16 GPa elastic modulus) designed for Example 4; wherein, Figure 5 (A) is the distribution of equivalent stress from the crown to the root along the pile-surrounding structure interface; Figure 5 (B) is the distribution of equivalent stress from buccal to lingual side along the red line in the cross section;

[0043] Figure 6 This is a picture of the bionic gradient zirconia reinforced resin post and core prepared in Example 5;

[0044] Figure 7 The stress distribution cloud diagram in the finite element model of the gradient post-core (6-4-3mm layering, 102-60-20GPa elastic modulus) designed for comparative example 1; wherein, Figure 7 (A) is the distribution of equivalent stress from the crown to the root along the pile-surrounding structure interface; Figure 7 (B) is the distribution of equivalent stress from buccal to lingual along the red line in the cross section.

[0045] Figure 8 This is a comparison chart of the in vitro flexural test of a commercial preformed fiber post and a biomimetic gradient zirconia reinforced resin post and core prepared in Example 5, wherein: Figure 8 (A) is the tooth fracture load diagram; Figure 8 (B) is a comparison diagram of failure mode distribution; Figure 8 (C) is the irreparable failure mode diagram of the prefabricated fiber post system; Figure 8 (D) is the repairable failure model of the bionic gradient zirconia reinforced resin post and core system; ns represents no statistical difference, and * represents statistical difference (P<0.05); DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The materials used in the examples and comparative examples of the present invention can all be purchased commercially.

[0047] Example 1

[0048] A method for preparing a bionic gradient zirconia reinforced resin block comprises the following steps:

[0049] (1) Constructing a zirconia-reinforced composite resin material system: a. Add 49.5 wt% UDMA, 49.5 wt% TEGDMA, 0.5 wt% CQ and 0.5 wt% DMAEMA into a beaker in sequence, and place the mixture on a shaker at 100 rpm / min in the dark for 72 h to obtain a resin matrix;

[0050] b. Stirring 30 wt% of the above resin matrix and 70 wt% of dental glass powder in a vacuum tube degassing mixer for 30 min to obtain a 0% zirconium oxide reinforced resin; stirring 30 wt% of the resin matrix, 65 wt% of the dental glass powder and 5 wt% of silanized zirconium oxide in a vacuum tube degassing mixer for 30 min to obtain a 5% zirconium oxide reinforced resin; stirring 30 wt% of the resin matrix, 60 wt% of the dental glass powder and 10 wt% of silanized zirconium oxide in a vacuum tube degassing mixer for 30 min to obtain a 10% zirconium oxide reinforced resin;

[0051] The silanized zirconium oxide is prepared by the following preparation method: weigh 5g of nano zirconium oxide (50nm), 100ml of pure water, and 100ml of anhydrous ethanol, and ultrasonicate for 30min; add 5mL of silane coupling agent (KH570) dropwise; stir magnetically at 70°C for 6h, and stand overnight; remove the supernatant, centrifuge at 10000rpm, 10min each time, wash 5 times with anhydrous ethanol, collect the powder; dry at 60°C, grind into powder, and obtain silanized zirconium oxide;

[0052] c. The zirconia reinforced resin is heated at a radiation intensity of 1400 to 1500 mW / cm 2 The LED curing lamp was used to irradiate the surface of the material for 40 seconds, followed by post-curing treatment at 60°C for 12 hours and heat treatment at 120°C for 12 hours to completely cure it. Thus, the elastic modulus of the obtained resins were 6.7 GPa for 0% zirconia reinforced resin, 8.5 GPa for 5% zirconia reinforced resin and 9.8 GPa for 10% zirconia reinforced resin.

[0053] (2) Model design of bionic gradient zirconia reinforced resin post and core: First, the model of the mandibular first premolar restored with a post and core crown was constructed using Solidworks software. The specific dimensions of the model were: anatomical root length 12.36 mm, anatomical crown height 6.7 mm, dentin shoulder height 1.5 mm, degree of polymerization 10°, tooth preparation shoulder located 1 mm above the cementoenamel junction, shoulder width 0.8 mm, 5 mm gutta-percha sealing area in the apical section of the root canal, periodontal membrane thickness 0.25 mm, alveolar bone located 2 mm below the CEJ, intrinsic alveolar bone thickness 0.25 mm, alveolar bone cortex thickness 1.5 mm, the rest is cancellous bone, and the resin adhesive layer thickness 0.1 mm. The dimensions of the gradient post and core were core height 3 mm, upper columnar post diameter 1.25 mm, length 2 mm, lower cone columnar post, length 8 mm, bottom diameter 0.9 mm, and total length of the post and core 13 mm.

[0054] Furthermore, the model was imported into the finite element analysis software Ansys Workbench for stress analysis. The post and core were given a three-stage gradient elastic modulus, specifically: 9.8 GPa for the upper 6 mm of the post and core, 8.5 GPa for the middle 4 mm, and 6.7 GPa for the apex 3 mm, i.e., a layered design of 6-4-3 mm and an elastic modulus design of 9.8-8.5-6.7 GPa. At the same time, material properties were given to other parts of the model, and the model was meshed; an oblique load of 200 N static load was applied to the buccal cusp lingual slope and 1.5 mm below the buccal cusp top, and the loading direction was 45° to the long axis of the tooth; the equivalent stress distribution of the model was analyzed, and the results showed uniform stress distribution from the crown to the root along the post-surrounding structure interface, and a slow transition of stress at the interface between the post and core and the surrounding structure, without obvious fluctuations, and uniform stress distribution ( Figure 1 );

[0055] (3) Preparation of bionic gradient zirconia reinforced resin block: According to the gradient post and core design of step (2), i.e., the layered design of 6-4-3 mm and the elastic modulus design of 9.8-8.5-6.7 GPa, the 9.8 GPa zirconia reinforced resin was first injected layer by layer into a stainless steel mold with a length of 14.0 mm, a width of 12.0 mm, and a height of 17.5 mm and a 1.0 mm marking scale inside. After each 1 mm injection, 9 points on the surface of the material were photocured, and each point was illuminated for 80 s. Then, the next layer of material was injected and the above curing process was repeated until the 10.5 mm thick 9.8 GPa zirconia reinforced resin was injected, and the excess 4.5 mm at the bottom was used for CAD / CAM cutting. When cutting the post and core, a connecting rod was set; then 8.5 GPa zirconia reinforced resin was continuously injected into the mold, and light-cured at 9 points on the material surface for every 1 mm injected, and each point was illuminated for 80 seconds until 4 mm was injected; then 6.7 GPa zirconia reinforced resin was injected, and light-cured at 9 points on the material surface for every 1 mm injected, and each point was illuminated for 80 seconds until 3 mm was injected; finally, the above resin block was taken out of the stainless steel mold, and post-cured at 60°C for 12 h and then heat-treated at 120°C for 12 h to completely cure it, and the final bionic gradient zirconia reinforced resin block (6-4-3 mm, 9.8-8.5-6.7 GPa) was obtained; SEM image ( Figure 2 ) shows that the gradient resin block has no voids and cracks at the delamination interface, showing excellent interlayer bonding strength.

[0056] Example 2

[0057] The preparation method of the bionic gradient zirconia reinforced resin block described in this embodiment refers to Example 1, and only the layering of the bionic gradient zirconia reinforced resin block is modified, that is, the layering gradient is 5-5-3mm, and the elastic modulus gradient is 9.8-8.5-6.7GPa. Specifically: first, the 9.8GPa zirconia reinforced resin is layered and injected into a stainless steel mold with a length of 14.0mm, a width of 12.0mm, and a height of 17.5mm and a 1.0mm marking scale inside. After each 1mm is injected, 9 points on the surface of the material are photocured, and each point is illuminated for 80s. Then the next layer of material is injected and the above curing process is repeated until the 9.5mm thick 9.8GPa zirconia reinforced resin is injected, wherein the excess 4.5mm at the bottom is used to set the connecting rod when CAD / CAM cuts the post and core; then 8.5GPa zirconia reinforced resin is continuously injected into the mold, After each injection of 1 mm, 9 points on the material surface were light-cured, and each point was illuminated for 80 seconds until 5 mm was injected; then 6.7 GPa zirconia reinforced resin was injected, and after each injection of 1 mm, 9 points on the material surface were light-cured, and each point was illuminated for 80 seconds until 3 mm was injected; finally, the resin block was taken out of the stainless steel mold, and post-cured at 60 ° C, 12 h and subsequently heat-treated at 120 ° C, 12 h to fully cure it, and the final bionic gradient zirconia reinforced resin block (5-5-3 mm, 9.8-8.5-6.7 GPa) was obtained; finite element analysis results ( Figure 3 ) showed that the gradient design in Example 2 was characterized by uniform stress distribution from the crown to the root along the post-surrounding structure interface, and a slow transition of stress at the interface between the post core and the surrounding structure without obvious fluctuation.

[0058] Example 3

[0059] The preparation method of the bionic gradient zirconia reinforced resin block described in this embodiment refers to Example 1, and only the layering of the bionic gradient zirconia reinforced resin block is modified, that is, the layering gradient is 7-3-3mm, and the elastic modulus gradient is 9.8-8.5-6.7GPa. Specifically: first, 9.8GPa zirconia reinforced resin is layered and injected into a stainless steel mold with a length of 14.0mm, a width of 12.0mm, and a height of 17.5mm and a 1.0mm marking scale inside. After each 1mm is injected, 9 points on the surface of the material are photocured, and each point is illuminated for 80s. Then the next layer of material is injected and the above curing process is repeated until the 11.5mm thick 9.8GPa zirconia reinforced resin is injected, wherein the excess 4.5mm at the bottom is used to set the connecting rod when CAD / CAM cuts the post and core; then 8.5GPa zirconia reinforced resin is continued to be injected into the mold, After each injection of 1 mm, 9 points on the material surface were light-cured, and each point was illuminated for 80 seconds until 3 mm was injected; then 6.7 GPa zirconia reinforced resin was injected, and after each injection of 1 mm, 9 points on the material surface were light-cured, and each point was illuminated for 80 seconds until 3 mm was injected; finally, the resin block was taken out of the stainless steel mold, and post-cured at 60 ° C, 12 h and subsequently heat-treated at 120 ° C, 12 h to fully cure it, and the final bionic gradient zirconia reinforced resin block (7-3-3 mm, 9.8-8.5-6.7 GPa) was obtained; finite element analysis results ( Figure 4 ) showed that the gradient design in Example 3 was characterized by uniform stress distribution from the crown to the root along the post-surrounding structure interface, and a slow transition of stress at the interface between the post core and the surrounding structure without obvious fluctuation.

[0060] Example 4

[0061] The preparation method of the bionic gradient zirconia reinforced resin block described in this embodiment refers to Example 1, and only the elastic modulus of the gradient zirconia reinforced resin block is modified, that is, the layered gradient of 6-4-3mm and the elastic modulus gradient of 20-18-16GPa. Specifically: first, 20GPa zirconia reinforced resin is layered and injected into a stainless steel mold with a length of 14mm, a width of 12mm, and a height of 17.5mm and a 1mm marking scale inside. After each 1mm is injected, 9 points on the surface of the material are photocured, and each point is illuminated for 80s. Then the next layer of material is injected and the above curing process is repeated until the 10.5mm thick 18GPa zirconia reinforced resin is injected, wherein the excess 4.5mm at the bottom is used to set the connecting rod when CAD / CAM cuts the post and core; then 8.5GPa zirconia reinforced resin is continued to be injected into the mold, and each injection is 1mm was injected, and light curing was performed at 9 points on the material surface, with each point irradiated for 80s until 4mm was injected; then 16GPa zirconia reinforced resin was injected, and light curing was performed at 9 points on the material surface every 1mm, with each point irradiated for 80s until 3mm was injected; finally, the resin block was taken out of the stainless steel mold, and post-curing treatment was performed at 60℃ for 12h and subsequent heat treatment was performed at 120℃ for 12h to completely cure it, and the final bionic gradient zirconia reinforced resin block (6-4-3mm, 20-18-16GPa) was obtained; finite element analysis results ( Figure 5 ) showed that the gradient design in Example 4 was characterized by uniform stress distribution from the crown to the root along the post-surrounding structure interface, and a slow stress transition at the interface between the post core and the surrounding structure without obvious fluctuation.

[0062] Example 5

[0063] The bionic gradient zirconia reinforced resin post and core ( Figure 6), prepared by cutting the bionic gradient zirconia reinforced resin block described in Example 1 using CAD / CAM technology. Specifically: the mandibular first premolar was collected, and the root canal preparation and filling were performed using the standard steps of root canal treatment, that is, the root canal was prepared to No. 20 using a K file, the root canal was prepared to No. 30 / 04 using an M3 system nickel-titanium file, and finally the root canal was filled with AH-plus root filling paste and gutta-percha tip; a four-wall defect tooth model was prepared, that is, the crown tooth tissue was removed until the remaining 1.5mm high dentin shoulder collar, and the dentin shoulder collar wall thickness was 1±0.05mm; then the shoulder was prepared, the shoulder was located 1mm above the enamel-cementum junction, the width was 0.9±0.05mm, and the degree of polymerization of the tooth preparation was 6-10°; then a No. 2 Peeso drill was used to prepare the post channel, and the 3M fiber post was used for preparation, step by step to the No. 2 drill, and the post channel was retained from the level of the dentin shoulder collar to the total length of 10mm of the root; after rinsing and drying the root canal, a silicone rubber post negative mold was made, and then a digital intraoral scanner Medit i700 scans the negative mold of the post channel to obtain the digital model of the tooth preparation and post channel;

[0064] Furthermore, the CAD software exocad is used to edit, repair and optimize the imported digital models of tooth preparation and post channel, and the post and core morphology is further designed, that is, the personalized post is consistent with the post channel morphology, the preparation type composed of the post and core and the remaining tooth tissue is consistent with the expected preparation type, and the edge of the post and core is consistent with the edge of the remaining tooth tissue;

[0065] Furthermore, the bionic gradient zirconia reinforced resin block described in Example 1 was cut using a CAM grinder Twinovation EasyMill I to obtain a bionic gradient zirconia reinforced resin post and core.

[0066] Comparative Example 1

[0067] The model design of the bionic gradient post and core described in this comparative example refers to Example 1, and only the elastic modulus design of the gradient post and core in the finite element model is modified, that is, the layered design of 6-4-3mm and the elastic modulus design of 102-61-21GPa. Specifically, the upper 6mm of the post and core is given an elastic modulus of 102GPa, the middle 4mm is given an elastic modulus of 61GPa, and the root apex is given an elastic modulus of 20GPa. Finite element analysis results ( Figure 7) shows that compared with the design in Example 1, the peak stress in Comparative Example 1 is significantly increased (56.4 GPa), the stress value in the middle and upper sections of the post-surrounding structure interface is relatively large, the stress fluctuation is obvious, and there is obvious stress concentration, which is located in the upper 1 / 3 of the root and near the cementoenamel junction. The equivalent stress distribution from the buccal to the lingual cross section shows that the span of the post-core elastic modulus is large, and the stress fluctuation is also large. There are obvious stress fluctuations in the range of 2.2-3.6 mm from the buccal side, which is specifically manifested as an increase from 19.72 MPa at 2.2 mm to a stress peak of 52.4 MPa within this range, and then a decrease to 9.6 MPa at 3.6 mm. Obviously, the bionic gradient resin block prepared in this comparative example does not match the gradient distribution of the elastic modulus of natural dentin itself.

[0068] Test experiment: Comparison of in vitro fracture resistance test of bionic gradient zirconia reinforced resin post and core

[0069] Figure 8 An in vitro flexural test was performed to compare the commonly used prefabricated RelyX Fiber post high-strength glass fiber post (3M ESPE, USA) in clinical practice with the bionic gradient zirconia reinforced resin post and core prepared in Example 5.

[0070] ① Post and core restoration: The experimental group used RelyX U200 resin cement to fix the biomimetic gradient zirconia reinforced resin gradient post and core, and chemically cured them for 10 minutes; the fiber post group used RelyX U200 resin cement, light-cured for 40 seconds, and Z350 composite resin (3M ESPE, USA) was used for core stacking, and light-cured for 40 seconds.

[0071] ② Crown restoration: After the post-core restoration was completed in two groups of ex vivo teeth (n=15), the digital intraoral scanner Mediti700 was used to scan the digital model of the post-core restored ex vivo teeth. The full crown restoration was then designed using the CAD software exocad, and the CAM grinder Twinovation EasyMill I was used to cut the glass ceramic block to obtain the full ceramic crown restoration. The full ceramic crown was bonded with RelyX U200 resin cement, and the occlusal surface, mesiodistal side, and buccal and lingual side were light-cured for 20 seconds each to complete the crown restoration.

[0072] ③ Fracture test: Use epoxy resin to embed the root of the excised tooth to 2mm below the cementoenamel junction (CEJ) to simulate the alveolar bone level. The long axis of the excised tooth is embedded vertically and upwardly in the horizontal plane, and the size of the epoxy resin is 20*20*20mm. The embedded excised tooth is tilted 45° and fixed on the universal testing machine Z100 for fracture test. A tungsten steel spherical indenter with a diameter of 5mm is used for static loading fracture test. The loading point is located at 1.5mm below the buccal lingual slope and the buccal cusp. The loading direction is 45° to the long axis of the tooth. The loading rate is 1mm / min. The test is stopped when the tooth breaks. The fracture load and failure mode (irreparable failure, reparable failure) when the tooth breaks are recorded. Taking 2mm below the CEJ as the boundary, the tooth fracture below this level is classified as irreparable failure, and above this level is reparable failure. The results of in vitro flexural test showed that the average fracture load of the gradient post group (609.70N) was slightly higher than that of the fiber post group (588.50N) ( Figure 8 A). Meanwhile, all prefabricated fiber posts showed irreparable failure mode, while mandibular premolars restored with bionic gradient zirconia reinforced resin posts and cores showed more restorable failure modes (5 / 15), and there was a statistically significant difference ( Figure 8 B). Representative cross-sectional images of failed samples in each group show that the fiber post does not match the root canal morphology, there is a gap between the canal wall and the post, the adhesive layer on the mesial and distal sides of the post is thicker, and the adhesive remains in the root canal after the fiber post is debonded ( Figure 8 C). The bionic gradient zirconia reinforced resin post-core group matched the root canal morphology and was tightly fitted to the surrounding canal wall. The adhesive layer was thin and uniform, and no post debonding occurred ( Figure 8 D).

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A design method for a bionic gradient zirconia reinforced resin block, characterized in that: The following steps are included: (1) Construction of zirconia reinforced composite resin material system: 20-40 wt% of resin matrix and 60-80 wt% of reinforcing filler are stirred in a vacuum tube degassing mixer and stored away from light for later use. Zirconia reinforced composite resin materials with processability and different elastic moduli can be obtained through preliminary light curing treatment, subsequent curing treatment and heating treatment; (2) Model design of bionic gradient zirconia reinforced resin post and core: Use Solidworks software to build a post-core crown restoration model, and further import the model into the finite element analysis software Ansys Workbench for stress analysis; set the gradient post and core layering to a three-stage design, assign the elastic modulus values ​​of different zirconia reinforced resins obtained in step (1) to the gradient post and core, and assign material properties to other parts of the model, and mesh the model. Then apply static loads to simulate the force on the teeth during chewing, analyze the stress distribution inside the teeth, adjust and optimize the layering and elastic modulus properties of the gradient post and core until the stress is evenly distributed inside the teeth, so as to screen out the bionic gradient post and core model that matches the tooth gradient; (3) Preparation of bionic gradient zirconia reinforced resin block: The zirconia reinforced resin with different elastic moduli obtained in step (1) is injected into the stainless steel mold according to the layered design of the bionic gradient post and core obtained in step (2). After each 1 mm of material is injected, a preliminary light curing treatment is performed, and then the next layer of material is injected and the above curing process is repeated until the entire mold is filled. Then, the resin block is taken out of the stainless steel mold, and post-curing treatment and heat treatment are performed on it to finally obtain a bionic gradient zirconia reinforced resin block; The reinforcing filler in step (1) comprises 0-10 wt% of silanized nano zirconium oxide and 90-100 wt% of dental glass powder; The three-stage design in step (2) is specifically as follows: the thickness of the first layer is 5 to 7 mm, the thickness of the second layer is 3 to 5 mm, and the thickness of the third layer is 3 mm; the three-stage design of the elastic modulus is: 9.8 to 20 GPa for the first layer, 8.5 to 18 GPa for the second layer, and 6.7 to 16 GPa for the third layer; the static load is 50 to 400 N, and the loading direction is horizontal loading, vertical loading, or oblique loading.

2. The design method of the bionic gradient zirconia reinforced resin block according to claim 1, characterized in that: The resin matrix in step (1) is composed of 97-99.5 wt% of resin monomer and 0.5-3 wt% of photoinitiator; the resin monomer is composed of (30-70) wt%: (30-70) wt% of dimethyl methacrylate urethane and dimethyl methacrylate triethylene glycol; the photoinitiator is composed of (40-60) wt%: (40-60) wt% of camphorquinone and N,N-dimethylaminoethyl methacrylate.

3. The design method of the bionic gradient zirconia reinforced resin block according to claim 1, characterized in that: The preparation process of silanized nano zirconium oxide is as follows: nano zirconium oxide, pure water, anhydrous ethanol and silane coupling agent are prepared according to a mass volume ratio of 1 to 5 g: 100 ml: 100 ml: 5 mL; firstly, nano zirconium oxide, pure water and anhydrous ethanol are ultrasonically mixed for 30 to 60 minutes, and the silane coupling agent is added dropwise; magnetic stirring is performed at 60 to 80° C. for 6 to 12 hours, and the mixture is allowed to stand overnight; the supernatant is removed, the mixture is centrifuged at 5000 to 10000 rpm for 10 to 30 minutes each time, and the mixture is washed with anhydrous ethanol for 5 times, and the powder is collected; the mixture is dried at 50 to 80° C., and the mixture is ground into powder to prepare the silanized nano zirconium oxide; The dental glass powder consists of 10 wt% of aluminum oxide, 10 wt% of boron oxide, 25 wt% of barium oxide and 55 wt% of silicon dioxide.

4. The design method of the bionic gradient zirconia reinforced resin block according to claim 1, characterized in that: The initial curing treatment described in step (1) is performed using a radiation intensity of 1400-1500 mW / cm 2 The LED curing lamp is used to irradiate the material surface at a depth of 0 to 1 mm for 40 seconds; the subsequent curing treatment temperature is 37 to 60 °C and the time is 12 to 24 hours; the heating treatment temperature is 120 to 150 °C and the time is 12 to 24 hours.

5. The design method of the bionic gradient zirconia reinforced resin block according to claim 1, characterized in that: The initial light curing treatment in step (3) is performed using a radiation intensity of 1400-1500 mW / cm 2 The LED curing lamp is used to irradiate 9 points at 0-1 mm on the surface of the material, and each point is irradiated for 80 s; the post-curing treatment temperature is 37-60 ℃ and the time is 12-24 h; the heat treatment temperature is 120-180 ℃ and the time is 12-24 h to fully cure it.

6. A bionic gradient zirconia reinforced resin block, characterized in that: The invention is obtained by designing according to the design method according to any one of claims 1 to 5.

7. A bionic gradient zirconia reinforced resin post and core, characterized in that: The post and core are obtained by cutting the bionic gradient zirconia reinforced resin block according to claim 6 through CAD / CAM.

8. Use of the bionic gradient zirconia reinforced resin post and core according to claim 7 in preparing a tooth defect repair material.

Citation Information

Patent Citations

  • Preparation method of denture film layer

    CN109512678A

  • Dental zirconia block having strength, translucency, and color gradient, and method for manufacturing same

    WO2016043378A1